IMPACTO DEL TLC ENTRE PERU Y COREA DEL SUR EN EL COMERCIO BILATERAL MEDIANTE EL MODELO DE GRAVEDAD - Suyón Olaya, Gino José; Collazos Alarcón, Mercedes Alejandrina (LACCEI, 2025)
This study assesses the impact of the Peru–South Korea Free Trade Agreement on the bilateral flows of both countries by employing a gravity model. It examines factors such as GDP, economic distance, tariffs, and population, evaluating their influence on trade exchanges. The analysis, based on bilateral trade data, shows that the treaty does not generate a significant impact, whereas GDP emerges as the main driver of trade. In contrast, economic distance stands out as a key structural barrier, linked to transport and logistics costs. The findings underscore the importance of complementary policies that address logistical and structural constraints, thereby fostering more effective commercial integration in distant economic and geographical contexts.